Character Formation of Fifth Grade Elementary School Students in Science Learning Through the Reflective Pedagogy Paradigm (RPP) Learning Model - Ajat Rukajat; Krisnayansyah (Postgraduate, University of Mataram, 2023)
This research aims to analyze the results of implementing the Reflective Pedagogy Paradigm (RPP) learning model in shaping student character at SDIT Al Kaffah Bekasi. This research is a case study. The research results show that the RPP learning model can facilitate the formation of student character. The problem in this research is formulated as follows. What are the results of the implementation of the Reflective Pedagogical Paradigm (RPP) learning model in facilitating student character formation at SDIT Al Kaffah Bekasi. This research aims to analyze the results of implementing the Reflective Pedagogy Paradigm (RPP) learning model in facilitating student character formation at SDIT Al Kaffah Bekasi. This research uses a qualitative aRPPoach with a case study method. A case study is research that emphasizes a deeper understanding of certain phenomena for individuals. Case studies are also useful in exploring problems that are unknown or little is known about a particular phenomenon